2021
DOI: 10.1038/s41467-021-26523-1
|View full text |Cite
|
Sign up to set email alerts
|

Electrically switchable van der Waals magnon valves

Abstract: Van der Waals magnets have emerged as a fertile ground for the exploration of highly tunable spin physics and spin-related technology. Two-dimensional (2D) magnons in van der Waals magnets are collective excitation of spins under strong confinement. Although considerable progress has been made in understanding 2D magnons, a crucial magnon device called the van der Waals magnon valve, in which the magnon signal can be completely and repeatedly turned on and off electrically, has yet to be realized. Here we demo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 36 publications
1
30
0
Order By: Relevance
“…In 2019, Xing et al (115) demonstrated long-distance magnon transport in a quasi-2D AF insulator MnPS3 via a nonlocal SSE. Subsequently, the nonlocal SSE in this system is shown to be turned on and off by an electrical current though a metal gate due to the nonlinear gate dependence (116). In 2020, Lee et al (163) showed that the insertion of a monolayer WSe2 between YIG and Pt layers enhances the LSSE voltage by a factor of ∼ 5 compared to that in an YIG/Pt system, showing a new avenue on SSE research with 2D transition dichalcogenide materials.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In 2019, Xing et al (115) demonstrated long-distance magnon transport in a quasi-2D AF insulator MnPS3 via a nonlocal SSE. Subsequently, the nonlocal SSE in this system is shown to be turned on and off by an electrical current though a metal gate due to the nonlinear gate dependence (116). In 2020, Lee et al (163) showed that the insertion of a monolayer WSe2 between YIG and Pt layers enhances the LSSE voltage by a factor of ∼ 5 compared to that in an YIG/Pt system, showing a new avenue on SSE research with 2D transition dichalcogenide materials.…”
Section: Discussionmentioning
confidence: 97%
“…The ℓm estimation may be affected by the locally distributed ∇T , which is discussed in References (95,96). So far, nonlocal SSEs are reported in several magnets such as ferrimagnetic YIG (94,95,96,97,98,99,100,101,102,103,104,105), Gd3Fe5O12 (106), Tm3Fe5O12 (107), NiFe2O4 (108), MgAl0.5Fe1.5O4 (109), antiferromagnetic Cr2O3 (111,112), α-Fe2O3 (37,110), NiO (34), YFeO3 (113), BiFeO3 (114), and 2D layered magnets MnPS3 (115,116) and CrBr3 (117).…”
Section: Sse As Probe Of Magnon Transportmentioning
confidence: 97%
“…The SMR effect has been observed in a system consisting of the van der Waals compound MoS 2 doped with Co impurities and Ta . However, experimental studies of the SMR effect in proper layered magnets are lacking so far, while a variety of studies on magneto-transport behavior in van der Waals magnetic compounds interfaced with HMs (Ta, Pt, and W) have been reported, highlighting the importance of such heterostructures for spintronic applications. We note here that, till date, most of such interfaces are assembled by sputtering of a HM layer on top of the selected van der Waals material, even though their structural characterization is scarcely reported.…”
Section: Introductionmentioning
confidence: 95%
“…In the van der Waals antiferromagnetic(AFM) materials, the magnon transport over several micrometers has been experimentally observed [22], and the spin Nernst effect due to the nontrival topology of magnon band has been theoretically discussed [23,24]. Furthermore, the ability to tune spin wave by gate has been demonstrated in the AFM bilayer CI 3 [25] and the magnon valve structure made of MnPS 3 [26], while the topological magnon insulator has been realized in CrXTe 3 (X = Si, Ge) compounds [27].…”
mentioning
confidence: 97%